Intra-arterial infusion chemotherapy versus isolated upper abdominal perfusion for advanced pancreatic cancer: a retrospective cohort study on 454 patients - Aigner, Karl R. (J Cancer Res Clin Oncol, 2019)
PURPOSE: The treatment of pancreatic carcinoma remains a challenge as prognosis is poor, even if confined to a single anatomical region. A regional treatment of pancreatic cancer with high drug concentrations at the tumor site may increase response behaviour. Intra-arterial administration of drugs generates homogenous drug distribution throughout the entire tumor volume. METHODS: We report on treatment outcome of 454 patients with advanced pancreatic carcinoma (WHO stage III: 174 patients, WHO stage IV: 280 patients). Patients have been separated to two different treatment protocols. The first group (n = 233 patients) has been treated via angiographically placed celiac axis catheters. The second group (n = 221 patients) had upper abdominal perfusion (UAP) with stopflow balloon catheters in aorta and vena cava. Both groups have been treated with a combination of cisplatin, adriamycin and mitomycin. RESULTS: For stage III pancreatic cancer, median survival rates of 8 and 12 months were reached with IA and UAP treatment, respectively. For stage IV pancreatic cancer, median survival rates of 7 and 8.5 months were reached with IA and UAP treatment, respectively. Resolution of ascites has been reached in all cases by UAP treatment. Toxicity was generally mild, WHO grade I or II, toxicity grade III or IV was only noted in patients with severe systemic pretreatment. The techniques, survival data and detailed results are demonstrated. CONCLUSIONS: Responsiveness of pancreatic cancer to regional chemotherapy is drug exposure dependent. The isolated perfusion procedure is superior to intra-arterial infusion in survival times. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00432-019-03019-6) contains supplementary material, which is available to authorized users.